Rhododendron tawangensis Sp. Nov. from Arunachal Pradesh - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1979)
A Rhododendron new to science, Rhododendron tawangensis Sahni & Naithani from Kameng District, Arunachal Pradesh, India is described. This species is allied to Rhododendron kendrickii Nutt., but differs in having papery bark,leaves smaller, 5-11 Ã— 1.5-2.5 cm, glaucous papillate underneath, tip blunt, mucronate, bracts cuspidate, capsule glandular hairy. This taxon is named after the place of collection i.e. Tawang in Kameng District from where it was recently collected.